Unique and different: autobiographies of two brazilian historians, Nelson Werneck Sodré and Boris Fausto - Lima da Silva, Wilton Carlos [UNESP]; Muniz Junior, Joao [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2023)
In the Brazilian historiographic tradition, autobiographical texts are very rare, except for some interviews, published in academic journals, in cultural supplements or specific collections, in addition to academic memorials, as required by some public competitions. In Brazil, as autobiographical works, understood as texts in the first person, of greater length and that cover public and private dimensions of the lives of historians, there are only two: Nelson Werneck Sodre (1911-1999) and Boris Fausto (1930-2023). Werneck is the author of five memoirs: Memorias de um soldado (1967), Memorias de um escritor (1970), A luta pela cultura (1990), A ofensiva reacionaria (1992) e A furia de Caliba: memorias do golpe de 64 (1994); while Fausto wrote two: Negocios e ocios: historia da imigracao (1997) e Memorias de um historiador de domingo (2010). From the life stories of these authors, we seek to identify narrative choices that reflect such distinctions as well as the proximity of epistemic virtues and performance within an area of expertise, so that such autobiographical narratives describe no only individual trajectories, as well as some intricacies of experience and academic discipline.
Keywords: Memory; Autobiography; Historiography; Performance; Epistemic Virtues